PROPOSED AMENDMENT OF BRITISH COMPANY LAW. - Murphy, Mary E. (The Accounting Review, 1946)
Abstract One of the most important reports in recent British experience is that of the Company Law Amendment Committee appointed by Great Britain Board of Trade in June 1943, to consider and report what modifications are desirable in the Companies Act 1929, as of January 1946. This document not only provides the best available resume of traditional and contemporary accounting and financial practice in Great Britain but offers eighteen major sets of recommendations for the improvement of company law. Although the detailed testimony of experts appearing before the committee may not merit the consideration of American accountants, specific proposals offered for the improvement of auditing and business procedures provide interesting contrasts between current English and American accounting techniques as well as vital areas open for improvement. Asserting its belief that the system of limited liability is essential to the nation's prosperity, the committee envisages the necessity of protecting the investor and enhancing his control over company managements without imposing unreasonable restraints upon ethical business.